基于改进PID算法的EM-CVT速比控制研究 - 蒋强; 柳洪义; 杨新桦; 程越 (Jixie chuandong)
Electromechanical control CVT（EM-CVT） is a new type of continuously variable transmission（CVT）,and its speed ratio follow error quality is an important parameter validated the performance of vehicle.In order to study the dynamical matching technology between EM-CVT and engine under the running state of vehicle,the special character of two working models is obtained by engine experiment,according to the mechanism of the EM-CVT,the relation between vehicle speed and speed ratio is theoretically analyzed.Based on the basic theory of PID control,the improved PID control algorithm is proposed for the speed ratio control of the EM-CVT,and experimental verification is made.The experimental results show that there is a significant effect on the system with this algorithm.